Simplified enzyme-linked immunosorbent assay for specific antibodies to respiratory syncytial virus. - Vaur, L (1986)
A simplified and reliable enzyme-linked immunosorbent assay (ELISA) was applied to the detection of serum antibodies against respiratory syncytial virus (RSV). RSV-infected cells were fixed and dried on 96-well microtiter plates and kept at 4 degrees C. The titers of reference sera were determined by endpoint dilution. A linear relation was found between the titers and the logarithm of absorbance values of sera diluted to 1:1,000 (r = 0.93, P less than 0.001). Measurement of RSV antibodies was done by using a single serum dilution (1:1,000) in conjunction with a standard curve. A strong correlation was found between complement fixation and ELISA results (r = 0.89, P less than 0.001). In addition, the ELISA method exhibited higher titers and a greater sensitivity than did complement fixation, although the applicability of the assay is limited with positive serum samples of low titer.